(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
Dairy calves must be fed appropriately to meet their nutritional needs, supporting optimal growth and development to achieve the recommended target age at first calving (AFC) of 24 months. Traditional restricted milk feeding practices suppress growth, contribute to negative welfare states and may result in malnutrition and immunosuppression. In this study a total of eight high yielding calves (four Holstein Friesian and four Sahiwal breed) whose average body weight was 44.8 kg and 58 kg respectively. The supplied calf starter was composed of maize crushed, rice polish, wheat bran, gram broken, mustard oil cake, vitamin mineral premix, molasses and common salt. Calf starter was supplied initially 0.25 kg/day/calf in equal halves to the experimental calves twice a day i.e. at 7.00 AM and 12.30 PM and gradually increase upto 1 kg/d/calf. Average body weight gain, wither height gain, body length gain, barrel height gain, and hip height gain in Sahiwal and Holstein Friesian calves were 65.97±1.04 Kg, 31.04±1.13 inch, 32.34±1.46 inch, 12.80±0.71 inch, 35.05±1.27 inch, and 53.61±2.41 Kg, 29.78±1.17 inch, 30.93±1.66 inch 11.78±0.66 inch, 33.44±1.41 inch respectively. Our study concluded to establish a consensus on calf feeding standards which support physiological function, facilitate weaning, support growth targets and ensure calf health and welfare is protected. Asian Australas. J. Biosci. Biotechnol. 2020, 5 (2), 60-64